Effect of Broccoli Residues Fermented with Probiotics on the Growth Performance and Health Status of Broilers Challenged with Clostridium Perfringens - N Liu; X Deng; C Liang; H Cai (Brazilian Journal of Poultry Science)
ABSTRACT This study aimed at investigating the effects of broccoli residues fermented with probiotics (BF) on the growth performance, immunity, and gut health in broilers challenged with Clostridium perfringens (C. perfringens). A total of 600 broilers (one day old) were randomly allotted into five treatments with six replicates of 20 birds each and were reared until 42 days of age. The treatments included a positive control (PC, fed a basal diet and reared on uncontaminated litter), a negative control (NC, birds reared on litter contaminated with C. perfringens and fed a basal diet), and NC plus BF at 25, 50 or 75 g/kg of diet. The BF contained yeast 3.1 × 107cfu/g, lactic acid bacteria 9.5 × 106cfu/g and Bacillus subtilis 3.5 × 106cfu/g. Birds in the NC group showed lower (p<0.05) feed intake and body weight gain, whereas BF supplementation recovered (p<0.05) the growth performance to the levels of PC group. Dietary BF at 50and 75 g/kg reduced (p<0.05) broiler mortality. Similarly, compared to the NC group, BF increased (p<0.05) immune organ weights and serum immunoglobulins A, G, and M to the levels of PC group. The ileal populations of Escherichia coli and Gram-negative bacteria were decreased (p<0.05) by BF to the levels of PC, and C. perfringens was also decreased (p<0.05) by BF. The serum profiles of mono- and di-amine oxidase were decreased (p<0.05) by BF. BF at 75 g/kg reduced (p<0.05) monoamine oxidase compared with the other BF doses. The results suggest that broccoli residues fermented with probiotics can be a novel biological feed additive to protect the performance and health of broilers against C. perfringens infection.